WebCrowds: An Authoring Tool for Crowd Simulation - Silva, Gabriel; Knob, Paulo; Montanha, Rubens; Musse, Soraia (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
Crowd simulation is an area of research largely used in the game industry. From the movement of a single NPC to the movement of an entire army, crowd simulation methods can be used to move agents through the environment while avoiding collisions with obstacles and between each other. Thus, it is important that game developers have access to crowd simulation tools that are both powerful and easy to use. In this paper, we present WebCrowds, an authoring tool for crowd simulation which can be used by anyone to build environments and simulate the movement of agents. The results achieved by our research suggest that WebCrowds is easy to use, delivers trustworthy simulation results, and can be used as an authoring tool for game developers who need to simulate crowds in their games.